Management of Pain in the United States-A Brief History and Implications for the Opioid Epidemic - Stephen A Bernard; Paul R Chelminski; Timothy J Ives; Shabbar I Ranapurwala (SAGE Publishing, 2018)
Pain management in the United States reflects attitudes to those in pain. Increased numbers of disabled veterans in the 1940s to 1960s led to an increased focus on pain and its treatment. The view of the person in pain has moved back and forth between a physiological construct to an individual with pain where perception may be related to social, emotional, and cultural factors. Conceptually, pain has both a medical basis and a political context, moving between, for example, objective evidence of disability due to pain and subjective concerns of malingering. In the 20th century, pain management became predominately pharmacologic. Perceptions of undertreatment led to increased use of opioids, at first for those with cancer-related pain and then later for noncancer pain without the multidimensional care that was intended. The increased use was related to exaggerated claims in the medical literature and by the pharmaceutical industry, of a lack of addiction in the setting of noncancer pain for these medications-a claim that was subsequently found to be false and deliberatively deceptive; an epidemic of opioid prescribing began in the 1990s. An alarming rise in deaths due to opioids has led to several efforts to decrease use, both in patients with noncancer conditions and in those with cancer and survivors of cancer.